Possibilities assessment of the film cluster in the Kaliningrad Oblast functioning - A. A. Gorshkova; M. I. Kosinova (Вестник университета)
The purpose of the study is to assess the problems and prospects of a film cluster in the Kaliningrad Oblast of the Russian Federation.   The following scientific research methods are used: analysis of scientific publications (articles), collection of primary information (conferences, round tables, foresight sessions, expert interviews), analysis of the regulatory framework. Empirical research methods are also involved: measuring quantitative data, conducting a survey and comparative analysis. The article substantiates the reasons why the Kaliningrad Oblast has been and remains an attractive region for film-makers. The analysis of available opportunities in the field of film production, film education, cast and other things is carried out. All aspects of the film industry are considered, including film festivals, film pitching and more. The work of the film commission is analyzed, in particular the rebate system introduced in 2017. The effectiveness of this system is evaluated in the light of the changes that occurred in it in 2020.